Individual Particle Characteristics, Optical Properties and Evolution of an Extreme Long‐Range Transported Biomass Burning Event in the European Arctic (Ny‐Ålesund, Svalbard Islands). Issue 5 (7th March 2020) - Moroni, B.; Ritter, C.; Crocchianti, S.; Markowicz, K.; Mazzola, M.; Becagli, S.; Traversi, R.; Krejci, R.; Tunved, P.; Cappelletti, D.
Abstract: This paper reports an exceptional biomass burning (BB) advection event from Alaska registered at Ny‐Ålesund from 10 to 17 July 2015 with particular interest on the influence of the airborne particle characteristics on the optical properties of the aerosol during the event. To this purpose we considered two DEKATI 12‐stage aerosol samples spanning the entire advection and analyzed them by scanning electron microscopy techniques. Aerosol chemical data and microphysical properties were also evaluated in order to correlate any change of individual particle characteristics with the bulk properties of the aerosol. The results of individual particle analysis depict a complex event characterized by a first phase (P1) of massive input of BB carbonaceous particles (i.e., tar balls, popcorn refractory particles, and organic particles), and by a second phase (P2) dominated by inorganic salts. The peculiar feature of this BB event is the exceptionally large grain size of the subspherical organic particles at the beginning of the event with respect to the background. At these conditions a significant increase of the scattering efficiency may occur even for a small increase of the size parameter. Results of the simulation of the complex refractive indices (n‐ik) confirm this evaluation. Aerosol evolution during the event resulted from the combination of three distinct occurrences: (a) progressive rotation of air mass circulation toward non‐BB source areas, (b) development of a thick fog layer in the planetary boundary layer, and (c) sea salt spray direct advection of local/regional provenance. Key Points: The case study is an exceptional biomass burning advection event from Alaska registered in the Arctic in July 2015 Results of analyses point at two distinct phases of the event dominated by organic carbon particles and inorganic salts, respectively Distinct aging effects involving organic carbon and inorganic salt particles at different relative humidity conditions are hypothesized